Modelling the moistening of the free troposphere during the northwestward progression of Indian monsoon onset. (23rd July 2018) - Menon, A.; Turner, A. G.; Martin, G. M.; MacLachlan, C.
Abstract : Understanding and prediction of Indian monsoon onset is of paramount importance for agricultural planning, which affects food production and the gross domestic product of the country. A recent observational study suggests that the progression of the Indian monsoon onset in a northwestward direction, which is perpendicular to the mean flow, is reinforced by the moistening of the free troposphere by pre‐monsoon showers and wetting of the land surface. As the onset progresses, the mid‐tropospheric dry layer is thought to be constantly moistened from below by detrainment from shallow cumulus and congestus clouds from the southeast. The dry layer becomes much shallower towards southeast India, making the profile closer to moist adiabatic, providing favourable conditions for deep cumulus convection. Increased moistening of the free troposphere thereby pushes the northern limit of moist convection northwestwards. Here, we examine the representation of this process in hindcast simulations from the fully coupled atmosphere–ocean seasonal forecast system of the UK Met Office, GloSea5. The model effectively captures the mid‐level dry‐air intrusion from the northwest that suppresses convection over the northwestern parts of India. We also show that detrainment from shallow convection, measured by moisture tendencies around the freezing level, acts to saturate the free troposphere ahead of the monsoon onset, eroding the dry layer from the southeast. This work suggests that initialized coupled models are capable of simulating dynamic and thermodynamic processes inherent in monsoon progression during the onset. Abstract : Northwest‐to‐southeast vertical section of ISCCP cloud fraction on pressure levels for cloud optical thickness, tau > 0.3 (shaded) and change in specific humidity (contoured) around (a) May 15 (averaged from May 13–17), (b) June 1 (averaged from May 30–June 3), (c) June 15 (averaged from June 13–17), (d) July 1 (averaged from June 29–July 3) and (e) July 15 (averaged from July 13–17). The orange dashed line represents the freezing level ( T =0°C).A recent observational study suggests that the Indian monsoon progression in a north‐westward direction perpendicular to the mean flow occurs due to a moistening of the free troposphere and wetting of land surface. Using an initialized fully‐coupled model, we show that detrainment from shallow convection, measured by moisture tendencies around the freezing level, acts to saturate the free troposphere ahead of monsoon onset, eroding the dry‐layer from the southeast; thereby pushing the northern limit of moist convection to move north‐westwards.